The Qur’an as a criterion for hadith-text examination - Khan, Israr Ahmad (London Academy of Iranian Studies, 2010)
Muslims rightly believe that the Qur’an and Sunnah (sayings and doings of the Last Prophet) are the most fundamental sources of Islamic thought, life, and civilization. Yet, they are not equal in terms of authenticity. The Qur’an is fully reliable without an iota of doubt. But Hadith literature contains both reliable and unreliable reports on the Prophet’s (s.a.w.) sayings and doings. In order to check authenticity of Hadith and Sunnah as recorded in sources Muslim scholars have developed some criteria, which basically serve the purpose of authentication of chain of reporters (sanad). As for the text of reports, no serious efforts have been made by Hadith scholars. The Qur’an must be considered as a criterion to check the position of text of Hadith reports. If there is an uncompromising conflict between Hadith-text and the Qur’an, Haith report must be rejected as fabricated and unreliable even though its chain of reporters appears authentic. In this article ten Hadiths have been selected from al-Bukhari’s and Muslim’s famous works of Hadith for text checking using the Qur’an as criterion. The selected Hadith in this article are: (1) lies attribute to Prophet Ibrahim, (2) predetermination of human destiny, (3) Irrelevance of Man’s deeds for entry into Paradise, (4) coercion in conversion to Islam, (5) Moses’ power to delay his death, (6) Moses’ condemnation of Adam’s error, (7) time involved in the creation of the universe, (8) Transfer of Muslims’ sins to Jews and Christians, (9) Eve as the root cause for women’s infidelity, and (10) women as source of bad omen. The author sees the texts of these Hadith as in sheer conflict with one or the other statement of the Qur’an hence he suggest that these Hadith are unreliable. The objective of this research is not to discredit the contribution of great Muslim scholars; it is rather to investigate further into the authenticity of Prophet Muhammad’s (s.a.w.) sayings and doings as compiled and recorded by Hadith scholars.